2023
DOI: 10.1021/acs.jafc.3c02027
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Alleviates Deoxynivalenol-Induced Intestinal Damage by Suppressing Inflammation and Ferroptosis in Mice

Abstract: Deoxynivalenol (DON), one of the most prevalent mycotoxins found in food and feed, can cause gastrointestinal inflammation and systemic immunosuppression, presenting a serious hazard to human and animal health. Quercetin (QUE) is a plant polyphenol with anti-inflammatory and antioxidant properties. In this research, we investigated the potential function of QUE as a treatment for DON-induced intestinal damage. Thirty male specific-pathogen-free BALB/c mice were randomly allocated to treatment with QUE (50 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Transmission electron microscopy (TEM) revealed structurally incomplete mitochondria with deficient cristae in cells from the DON-treated groups (Figure G,H and Table S5). Oxidative stress constitutes a significant aspect of cellular damage induced by DON . In the groups treated with DON, there was an elevation in H 2 O 2 levels, accompanied by a reduction in the levels of CAT, T-AOC, and T-SOD (Figure I–L).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) revealed structurally incomplete mitochondria with deficient cristae in cells from the DON-treated groups (Figure G,H and Table S5). Oxidative stress constitutes a significant aspect of cellular damage induced by DON . In the groups treated with DON, there was an elevation in H 2 O 2 levels, accompanied by a reduction in the levels of CAT, T-AOC, and T-SOD (Figure I–L).…”
Section: Resultsmentioning
confidence: 99%
“…The oral median lethal dosage of DON was 46 mg/kg. The dose of DON used was based on the recent report, at doses of 150 μg/kg (1/300 LD50) and 2300 μg/kg (1/20 LD50). Mice (eight per group) were separated into three groups as follows: Con (control), DON150 (150 μg/kg b.w.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have substantiated their positive impact on human health, underscoring their potent antioxidant, anti-inflammatory, and anticancer properties. Consequently, it is unsurprising that researchers have shown considerable interest in these compounds, as they demonstrate substantial potential in inhibiting ferroptosis [ 95 , 118 , 197 , 306 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ferroptosis, a unique form of non-apoptotic cell death, can be initiated by the accumulation of iron and production of reactive oxygen species (ROS) from lipid peroxidation 31 . Several studies have identified ferroptosis as an important contributor to the occurrence and progression of various diseases and inhibiting ferroptosis may lessen inflammatory response and intestinal epithelial cells (IECs) injury in IBD 32 - 34 . However, it remains unclear whether the intestinal cGAS-STING pathway is involved in IEC ferroptosis during colitis and how SP/NK1R signaling affects it in maintaining epithelial homeostasis.…”
Section: Introductionmentioning
confidence: 99%